Research on the impact of green finance on collaborative governance of pollution reduction and carbon reduction - Ke Lu; Dongri Han; Chaoyang Li; Yiming Chen (Scientific Reports)
Abstract Collaborative governance of pollution reduction and carbon reduction is an important measure to achieve the goal of “green ecological civilization construction” in China. This paper utilizes the coupling coordination degree model to assess the level of collaborative governance of pollution reduction and carbon reduction, while the entropy method is employed to quantify the green finance development index. Using provincial panel data from 2013 to 2022 in China, this paper initially explores the direct relationship between green finance and collaborative governance of pollution reduction and carbon reduction through a baseline regression model. Secondly, considering the heterogeneity in geographical location and energy endowment, this paper categorizes the sample provinces into distinct regions to conduct heterogeneous analysis. Lastly, employing the threshold regression model, this paper examines the non-linear impact of green finance on the collaborative governance of pollution and carbon reduction, with green finance, green technology innovation, and new energy industry development as the threshold variables. The following results are obtained through the test: (1) Green finance significantly and directly impacts the collaborative governance of pollution reduction and carbon reduction. (2) The effect of green finance on collaborative governance of pollution reduction and carbon reduction varies by geographical location and energy endowment, showing a pattern of “Central > Western > Eastern > Northeast” and “Energy-rich areas > Non-energy-rich areas.” (3) Considering regional heterogeneity, green finance exhibits varying threshold effects on collaborative governance of pollution reduction and carbon reduction. In the case of low green finance development level, high green technology innovation, and high new energy industry development, green finance can have a more positive influence. The study results of this paper offer a certain reference value for the government to formulate relevant policies and create a good ecological environment.